TRANSFER RNA: A COMPARISON BY GEL ELECTROPHORESIS OF THE TRNA IN HELA CYTOPLASM, HELA MITOCHONDRIAL FRACTION, AND E. coli - Knight, E. (1969)
A class of transfer RNA separable from the majority of transfer RNA by gel electrophoresis has been observed in E. coli and in the mitochondrial fraction of HeLa cells but not in HeLa cytoplasm. The size of this class of transfer RNA, as judged by its mobility on polyacrylamide gel, is intermediate between the major part of the transfer RNA and 5S RNA. It exists in part associated with the ribosomes, and its amino acid acceptor activity is different from the major class of transfer RNA.